Analisis Pemikiran Al-Ghazali Tentang Ekonomi Islam - Nurgantii Nurgantii; Audia Adinda Syafrani; Irhamsyah Putra Pasaribu; Muhammad Nur Tondi; Riska Sri Lestari (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Al-Ghazali is one of the most influential scholars in the field of Islamic economics. Al-Mustashfa Mizan, al-Amal, At-Tibr al-Masbuk fi al-Nasihah al-Muluk, and Ihya Ulumuddin, Al-Ghazali's monumental works explain the subtle aspects of Islamic economics in a straightforward manner. Because economic growth is seen as one aspect of the social obligations that have been established by God. Al-Ghazali emphasizes stability, justice and peace in these verses as the basis for a healthy economy in the fields of production, consumption and distribution. Therefore, it is very important for every country to fully embrace it.